Interleukin‐22 serum levels are elevated in active scleritis. (24th March 2016) - Sainz‐de‐la‐Maza, Maite; Molins, Blanca; Mesquida, Marina; Llorenç, Victor; Zarranz‐Ventura, Javier; Sala‐Puigdollers, Anna; Matas, Jessica; Adan, Alfredo; Foster, C. Stephen
Abstract: Purpose: To evaluate serum cytokine profile from patients with active scleritis in a two‐centre prospective case–control study. Methods: The serum of 20 active scleritis patients not treated with any local, periocular, or systemic immunomodulatory therapy (IMT) was analysed with multiplex assay to determine the levels of 11 cytokines interleukin (IL)‐1 β, IL‐6, IL‐2, IFN‐ γ, IL‐10, IL‐12p40, IL‐13, IL‐17A, IL‐5, TNF‐ α, and TNF‐ β, and with ELISA to determine the levels of TGF‐ β 1, IL‐22, and IL‐23. Twenty‐five age‐matched healthy volunteers were used as controls. In a subgroup of 13 patients with active disease, a second serum sample was obtained when the disease was inactive and levels of IL‐22 were determined. Serum IL‐22 levels from patients with active scleritis were correlated with type of scleritis (non‐necrotizing and necrotizing), degree of inflammation (0–4+ :≤2+ and >2+), and associated systemic disease. Results: Serum levels of IL‐22 were elevated in active scleritis patients compared to controls (6.41 ± 1.52 pg/ml versus 1.93 ± 0.39 pg/ml, p = 0.012) and significantly decreased after scleritis remission with the use of IMT (p = 0.005). There was no statistical association with scleritis type, degree of inflammation, or associated systemic disease. The serum levels of other cytokines were not significantly different from controls. Conclusion: In our study cohort, IL‐22 serum levels were significantly elevated in active scleritis patients compared to controls and decreased significantly after remission. Our results suggest that IL‐22, a T helper (Th) 17‐ and Th22‐ derived cytokine, may play a critical role in the physiopathology of scleritis.